Teologia e pintura: um olhar teológico sobre a obra "Marília de Dirceu" de Guignard - Blain, Sergio (2011)
The aim of this work is to explain, based on the art of painting, the contribution of distinct peoples and their cultures (the Brazilian culture, in the present case) in building the kingdom of God among us. The mankind was raised in order to live in fraternal communion. The solidarity doctrine, which is consummated within the incarnation of the son, extends the will and the path of salvation. According to Paul it should have unit within the diversity of the Christian community. Anyone and every culture such as, Jews, Greeks, slaves, freemen, men and, women, can find a place in the Church. (Cf Gl 3,28) shows the contribution of the Catholic Church in forming the Brazilian thoughts, mainly the ones expressed by the firsts painters, sculptors, architects and, educators of Brazil. The Catholic Church also contributed to the fight for a progressive mentality of assimilation of different cultures (inculturation), based on the respect for ethical values, moral and artistic values of each ethnic group. The Catholic Church also tries to indicate that when the moral values of any culture are oriented to the common good, we can find all the elements of humanity necessaries to the deployment of respect and universal brotherhood, or as it was said before, the kingdom of God in the men life